Conceptions of traditionalist medicine and herbalism in the Tradiciones peruanas by Ricardo Palma - Bedoya Castillo, María Paula (2019)
This article will analyze the traditions «El abad de Lunahuaná» and «Los panecitos de San Nicolás», texts that present different conceptions of the traditionalist medicine booming at the time when they were written. The herbal treatments of that time and their changes in the present day will also be discussed.